Udvikling af præ-professionel identitet i en ung uddannelse: Ernæring og sundhedsuddannelsen som case - Lang, Nanna R.; Nielsen, Birgitte L.; Grosen, Trine H.; Høyer, Hanne (Tidsskrift for Professionsstudier, 2023)
This paper examines pre-professional identity (PPI) in a young professional education. PPI is a matter of students’ dawning professional identity during education. The empirical material are group interviews with nutrition and health students and educators as well as participatory observation. Data is analysed using reflexive thematic analysis. The analysis shows that it is difficult for students and educators to identify the characteristics of the profession of nutrition and health. However, they do point to these unifying elements: A Bachelor of Nutrition and Health holds knowledge of nutrition and health, and works with foods, counselling and communication based on evidence and with respect and care of the individual. The analysis also shows that it impacts the understanding and development of PPI in young professional educations that students and educators find the profession broad. Therefore, it might be of relevance to facilitate students’ reflections on PPI during their education. This could be done by facilitating room for reflection across students, lecturers, head of education, and practitioners, and through a logbook for professional identity.